2021
DOI: 10.3390/diagnostics11111999
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Circulating Biomarkers for Patients Undergoing Resection of Colorectal Liver Metastases

Abstract: Surgical tumor resection has evolved as a potentially curative therapy for patients with resectable colorectal liver metastases (CRLM). However, disease recurrence is common and the available preoperative stratification strategies are often imprecise to identify the ideal candidates for surgical treatment, resulting in a postoperative 5-year survival rate below 50%. Data on the prognostic value of CEA, CA19-9 and other common laboratory parameters after CRLM resection are scarce and partly inconclusive. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
(45 reference statements)
0
5
0
Order By: Relevance
“…There were 278 potentially eligible publications on post‐diagnosis adiposity and colorectal cancer outcomes. We excluded 193 publications 45–237 due to specific reasons related to the synthesis (Supplementary Table 5). Finally, 85 publications…”
Section: Resultsmentioning
confidence: 99%
“…There were 278 potentially eligible publications on post‐diagnosis adiposity and colorectal cancer outcomes. We excluded 193 publications 45–237 due to specific reasons related to the synthesis (Supplementary Table 5). Finally, 85 publications…”
Section: Resultsmentioning
confidence: 99%
“…Data on the prognostic value of CEA, CA19-9, and other common laboratory parameters in assessing CRLM are scarce, with some studies being inconclusive or concluding otherwise. Recent literature [ 28 ] suggests that CEA may have some value in identifying patients with worse prognosis after CRLM resection. Regarding the absence of positive results for , we consider that it may be caused by the insufficient number of patients we collected.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of peripheral blood samples has been suggested as a sensitive and non-invasive method for biomarker determinations in screening cancer. Previous studies have indicated that carcinoembryonic antigen (CEA) and carbohydrate antigen199 (CA199) were significantly elevated in mCRC patients ( 8 , 9 ). In addition to the CEA and/or the CA199, the heat shock protein 90 alpha (Hsp90α) has also been reported to be linked to tumors.…”
Section: Introductionmentioning
confidence: 99%